2016
DOI: 10.1134/s0016793216030075
|View full text |Cite
|
Sign up to set email alerts
|

Comparative quality analysis of models of total electron content in the ionosphere

Abstract: We present a brief description and comparative analysis of the Klobuchar, GEMTEC, and NTCM GL models of total electron content in the ionosphere. The quality of model performance against experimental data on the total electron content is compared. Statistical estimates for the residual positioning error are obtained for each of these models on the basis of the international Global Navigation Satellite Sys tems (GNSS) Service data. The GEMTEC and NTCM GL models are shown to have a higher positioning accuracy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…Ivanov et al [ 36 ] showed that GEMTEC overperformed the Klobuchar model for 2003–2012 (at the Asian mid-latitudes). Because GEMTEC is a GIM-based model involving data up to 2012, we could expect a reduction in its precision after that period.…”
Section: Discussionmentioning
confidence: 99%
“…Ivanov et al [ 36 ] showed that GEMTEC overperformed the Klobuchar model for 2003–2012 (at the Asian mid-latitudes). Because GEMTEC is a GIM-based model involving data up to 2012, we could expect a reduction in its precision after that period.…”
Section: Discussionmentioning
confidence: 99%
“…Детальное описание модели GEMTEC представлено в статье [Ivanov et al, 2011]. Лежащий в ее основе метод главных компонент позволяет существенно сжать исходный массив данных и отфильтровать содержащиеся в них шумовые флуктуации.…”
Section: тестирование модели Gemtecunclassified
“…Две такие модели были разработаны практически одновременно и независимо несколько лет назад. Речь идет о модели NTCM_GL [Jakowski et al, 2011] и созданной авторами данной статьи модели GEMTEC [Ivanov et al, 2011].…”
Section: Introductionunclassified
See 1 more Smart Citation